If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4) + 10 = 2x + -12 Reorder the terms: 6(-4 + x) + 10 = 2x + -12 (-4 * 6 + x * 6) + 10 = 2x + -12 (-24 + 6x) + 10 = 2x + -12 Reorder the terms: -24 + 10 + 6x = 2x + -12 Combine like terms: -24 + 10 = -14 -14 + 6x = 2x + -12 Reorder the terms: -14 + 6x = -12 + 2x Solving -14 + 6x = -12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -14 + 6x + -2x = -12 + 2x + -2x Combine like terms: 6x + -2x = 4x -14 + 4x = -12 + 2x + -2x Combine like terms: 2x + -2x = 0 -14 + 4x = -12 + 0 -14 + 4x = -12 Add '14' to each side of the equation. -14 + 14 + 4x = -12 + 14 Combine like terms: -14 + 14 = 0 0 + 4x = -12 + 14 4x = -12 + 14 Combine like terms: -12 + 14 = 2 4x = 2 Divide each side by '4'. x = 0.5 Simplifying x = 0.5
| 115x+25+10x=1400 | | 11=-3-x | | 4v=7 | | 2(m-3)-(2m+6)= | | 9c+8=3 | | x+(x+7)=60 | | N^2-9n+19=0 | | -11=4-8x+1 | | 5n-7=4 | | 48=x^4-5x^2+4 | | 8b+11+2b=2b+2 | | 2(x+2)=16+4x | | 2y=(k+4)x-1 | | 2=8(h-5) | | 0.8+0.4=12 | | 0.8x=0.4 | | 2=3(i-5) | | -9=6a+1-a | | 18.4+8=t | | 3(x-5)=5x-(3-y) | | 3(7x+3)-11(2x+1)=-x-2 | | 0=6x^2+6x-120 | | 4n+3=-12 | | 9=3k-5 | | .5x+42=50 | | 18-w-13=-20 | | -3k-7k=20 | | 5.2+8=t | | 22+4n-2=n+2 | | 6m^2+9m^3=0 | | 3=28-6x | | 9=3k+5 |